(untitled) - Liu, Weifeng (Hoboken, N.J., 2004)
This book provides a comprehensive reference on all aspects of integrated circuit (IC) socket technology. It's intended mainly for IC managers and engineers who need specific and detailed information about sockets but are bewildered by the variety and scope of contact designs and features. Component socket properties and materials are covered, as well as component sockets for PTH, J-Leaded, Gull-Wing, BGA and LGA packages, failure modes and mechanisms, socket testing and qualification, and a section on reliability assessment.
Keywords: Printed circuits,Electric connectors.,Microelectronic packaging; Equipment and supplies